2017
DOI: 10.1002/chem.201701224
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivation of Anticancer Ru Complexes in Deep Tissue: How Deep Can We Go?

Abstract: Activation of anticancer therapeutics such as ruthenium (Ru) complexes is currently a topic of intense investigation. The success of phototherapy relies on photoactivation of therapeutics after the light passes through skin and tissue. In this paper, the photoactivation of anticancer Ru complexes with 671-nm red light through tissue of different thicknesses was studied. Four photoactivatable Ru complexes with different absorption wavelengths were synthesized. Two of them (Ru3 and Ru4) were responsive to wavele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 56 publications
0
45
0
Order By: Relevance
“…Red light irradiation (656 nm) of the micelles red‐shifted the MLCT band from 519 nm (λ max of PEG‐ b ‐P(CPH‐ co ‐RuCHL)) to 576 nm (λ max of [Ru(CHLtpy)(biq)(H 2 O)] 2+ ) (Figure c). The detectable spectral change can be achieved less than 0.5 h and the change was identical to that of the photocleavage of similar Ru complexes, suggesting [Ru(CHLtpy)(biq)(H 2 O)] 2+ was cleaved from the polymer . Additionally, the result from UV–Vis absorption spectroscopy indicated that the photoreaction can be precisely controlled by the irradiation dose (Figure S22a, Supporting Information).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Red light irradiation (656 nm) of the micelles red‐shifted the MLCT band from 519 nm (λ max of PEG‐ b ‐P(CPH‐ co ‐RuCHL)) to 576 nm (λ max of [Ru(CHLtpy)(biq)(H 2 O)] 2+ ) (Figure c). The detectable spectral change can be achieved less than 0.5 h and the change was identical to that of the photocleavage of similar Ru complexes, suggesting [Ru(CHLtpy)(biq)(H 2 O)] 2+ was cleaved from the polymer . Additionally, the result from UV–Vis absorption spectroscopy indicated that the photoreaction can be precisely controlled by the irradiation dose (Figure S22a, Supporting Information).…”
Section: Resultsmentioning
confidence: 73%
“…Red‐light‐responsive PEG‐ b ‐P(CPH‐ co ‐RuCHL) is better suited than conventional UV or short‐wavelength visible light‐responsive polymers for biomedical applications because red light can penetrate deeper into tissue . We have demonstrated that red light activated Ru complexes with similar responsive wavelengths to PEG‐ b ‐P(CPH‐ co ‐RuCHL) after red light passed through tissue with a thickness up to 16 mm . Because PEG‐ b ‐P(CPH‐ co ‐RuCHL) exhibits improved biocompatibility via PEGylation, enhanced anticancer efficiency via drug conjugation, facilitated endocytosis via micellization, and deep‐tissue activation via red light irradiation, PEG‐ b ‐P(CPH‐ co ‐RuCHL) is a promising candidate for PACT against hypoxic tumors in vivo.…”
Section: Introductionmentioning
confidence: 98%
“…[ 100 ] Recent work on ruthenium polypyridyl‐containing micelles demonstrated their use in vivo as well. [ 101–103 ] Upon degradation, the micelles released ruthenium photoproducts into local tissue and the bloodstream; no ruthenium buildup in any major organ (i.e., liver, spleen, kidney, lung) or tissue damage was observed.…”
Section: Perspectivesmentioning
confidence: 99%
“…2,16,20 For example, our group synthesized four photoresponsive Ru complexes and studied the photoactivation of these complexes in deep tissue. 21 Two of them (Ru3 and Ru4) have absorption tails in the "therapeutic window" and can be activated using red light (Fig. 1a).…”
Section: Deep-tissue Photoactivation Of Ru Complexes With Red Lightmentioning
confidence: 99%